2020
DOI: 10.1186/s40942-020-00219-y
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration in systemic lupus erythematosus: layer by layer retinal study using optical coherence tomography

Abstract: Background Systemic lupus erythematosus (SLE) is a chronic, autoimmune and multisystemic disease. Recent studies with functional and structural magnetic resonance imaging and cognitive tests report an unexpectedly high frequency of central nervous system involvement, even in patients with asymptomatic SLE. The purpose of this study was to identify early signs of retinal neurodegeneration by comparing the thickness of the peripapillary retinal nerve fiber layer (pRNFL) and all macular layers bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 45 publications
3
16
1
Order By: Relevance
“…Consistent with the results from Dias-Santos et al [ 17 ], we observed that the photoreceptor cell layer was significantly thinner in SLE patients with DLD compared to patients without DLD. As a tissue with high metabolic needs, the function of the cones and rods is directly dependent on the neighboring nourishing choriocapillaris [ 6 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Consistent with the results from Dias-Santos et al [ 17 ], we observed that the photoreceptor cell layer was significantly thinner in SLE patients with DLD compared to patients without DLD. As a tissue with high metabolic needs, the function of the cones and rods is directly dependent on the neighboring nourishing choriocapillaris [ 6 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the results from Dias-Santos et al [ 17 ], we observed that the photoreceptor cell layer was significantly thinner in SLE patients with DLD compared to patients without DLD. As a tissue with high metabolic needs, the function of the cones and rods is directly dependent on the neighboring nourishing choriocapillaris [ 6 , 17 , 18 ]. As described above, SLE can involve the choroidal structures and blood flow and thus, leading to ischemia and atrophy in the retinal segments they supply with oxygen and nutrients [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations